2021
DOI: 10.1186/s40249-021-00819-2
|View full text |Cite
|
Sign up to set email alerts
|

Bedaquiline-containing regimens in patients with pulmonary multidrug-resistant tuberculosis in China: focus on the safety

Abstract: Background World Health Organization recommends countries introducing new drug and short treatment regimen for drug resistant tuberculosis (DR-TB) should develop and implement a system for active pharmacovigilance that allows for detection, reporting and management of adverse events. The aim of the study is to evaluate the frequency and severity of adverse events (AEs) of bedaquiline-containing regimen in a cohort of Chinese patients with multidrug-resistant (MDR)/extensively drug-resistant (XD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 21 publications
2
12
0
2
Order By: Relevance
“…This study investigated the safety of bedaquiline; patients who were without a bedaquiline regime have a higher chance of adverse events (OR 3.54; 95% CI 1.23-10.1) than the other group. The results of this study are consistent with previous studies ( Gao et al, 2021 ; Mbuagbaw et al, 2019 ; Lan et al, 2020 ). This indicates that bedaquiline added to a background regimen can improve the rate of successful outcomes and quality of life.…”
Section: Discussionsupporting
confidence: 94%
“…This study investigated the safety of bedaquiline; patients who were without a bedaquiline regime have a higher chance of adverse events (OR 3.54; 95% CI 1.23-10.1) than the other group. The results of this study are consistent with previous studies ( Gao et al, 2021 ; Mbuagbaw et al, 2019 ; Lan et al, 2020 ). This indicates that bedaquiline added to a background regimen can improve the rate of successful outcomes and quality of life.…”
Section: Discussionsupporting
confidence: 94%
“…If a serious adverse event (SAE) of the anti-TB regimen occurred, the patient would receive inpatient management. The SAE in both arms was defined as a life-threatening event resulting in hospitalization, prolongation of hospitalization, (persistent or significant) disability, or death [9,13]. By the end of the 2-year period, the patient might achieve favourable outcomes.…”
Section: Model Structurementioning
confidence: 99%
“…The BDQ-based regimens are also reported to be better tolerated than conventional therapy. A large cohort analysis in China (n = 1162 received BDQ-based regimens) reported that 66.9% of the adverse events were classified as minor events (grade 1-2) [13]. QTprolongation was reported infrequently (0.4%) [12], and gradually declined after BDQ treatment was discontinued [14].…”
Section: Introductionmentioning
confidence: 99%
“…Patients who meet all the following inclusion criteria will be considered for recruitment: (1) M.tb strain positive diagnosed with culture from sputum or bronchoalveolar lavage fluid as identified using a BACTEC MGIT 960 automated mycobacterial detection system (Becton, Dickinson and 6) No history of allergies to drugs involved in the trial. (7) Patients must agree to the treatment voluntarily and provide signed informed consent.…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…Long therapeutic schedule includes the third-generation fluoroquinolone and a second-line injectable combined with at least five anti-tuberculosis medications considered to be effective, based on drug susceptibility testing (DST), or at least four considered effective plus pyrazinamide (PZA or Z) [ 6 ]. Adverse events (AEs) are thought to be the most important clinical consideration in the longer regimen, such as elevated liver enzymes, gastrointestinal disorders, and ototoxicity [ 7 ]. More than half of MDR-PTB patients experience one or more AEs during treatment procession [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%